Constituents of Erythrina - a Potential Source of Secondary Metabolities: A Review (Bangladesh Pharmaceutical Journal, 2016)
The genus Erythrina is a potential source of chemical constituents, many of which medicinal properties. Although some reviews on chemical constituents of particular Erythrina species could be found, no detailed review covering the chemistry of different Erythrina species has been reported to the best of my knowledge. Therefore, the aim of this review was to compile the phytoconstituents reported from various species of Erythrina. A total of 155 secondary metabolites have been published from 15 species of Erythrina. Among them E. subumbrans and E. variegata consist of the highest number of chemical constituents.Bangladesh Pharmaceutical Journal 19(2): 237-253, 2016